2008
DOI: 10.1016/j.ygcen.2007.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning of pituitary glycoprotein α-subunit and follicle stimulating hormone and chorionic gonadotropin β-subunits from New World squirrel monkey and owl monkey

Abstract: The goal of this study was to characterize the gonadotropins expressed in pituitary glands of the New World squirrel monkey (Saimiri sp.) and owl monkey (Aotus sp.). The various subunits were amplified from total RNA from squirrel monkey and owl monkey pituitary glands by reverse transcription-polymerase chain reaction and the deduced amino acid sequences compared to those of other species. Mature squirrel monkey and owl monkey glycoprotein hormone α-polypeptides (96 amino acids in length) were determined to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 39 publications
(35 reference statements)
0
14
0
Order By: Relevance
“…For the common marmoset, which serves as a preferred primate model in biomedicine in general and in reproductive research specifically (Moore et al 1985, Hearn 1986, Saunders et al 1987, Smith et al 1987, Hearn et al 1988, we previously found that CG is strongly expressed in the marmoset pituitary instead of LH (Muller et al 2004b). This finding was confirmed when only CGB but not LHB gene expression was found in the NWM Ma's night monkey (Aotus nancymaae) and the brown squirrel monkey (Saimiri boliviensis; Scammell et al 2008). An investigation of CGB gene copy numbers in different primate taxa revealed that CGB is a singlecopy gene in NWM (Maston & Ruvolo 2002), which raises the question 'how is the marmoset able to differentially regulate CGB expression in the pituitary and placenta?'…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…For the common marmoset, which serves as a preferred primate model in biomedicine in general and in reproductive research specifically (Moore et al 1985, Hearn 1986, Saunders et al 1987, Smith et al 1987, Hearn et al 1988, we previously found that CG is strongly expressed in the marmoset pituitary instead of LH (Muller et al 2004b). This finding was confirmed when only CGB but not LHB gene expression was found in the NWM Ma's night monkey (Aotus nancymaae) and the brown squirrel monkey (Saimiri boliviensis; Scammell et al 2008). An investigation of CGB gene copy numbers in different primate taxa revealed that CGB is a singlecopy gene in NWM (Maston & Ruvolo 2002), which raises the question 'how is the marmoset able to differentially regulate CGB expression in the pituitary and placenta?'…”
Section: Discussionmentioning
confidence: 60%
“…Furthermore, human LHB and marmoset CGB promoters show similar GNRH responsiveness and identical transcription factor binding sites (TFBS) in the core promoter of the pituitary (Henke et al 2007). Findings were similar to that of other NWM species as well (Scammell et al 2008, Vasauskas et al 2011. In contrast, human placental CGB transcription starts 365 bp upstream of exon 1 so that the human CGB 5 0 -UTR encompasses the region that would serve as a regulatory region in paralogous human LHB and orthologous marmoset CGB.…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…Anterior pituitary hormones play a key role in reproductive physiology (Bugbee et al, 1931). Gonadotropin-releasing hormone (GnRH) binds to gonadotropes to stimulate synthesis and secretion of two glycoprotein hormones: follicle stimulating hormone (FSH) and luteinizing hormone (LH) by the anterior pituitary (Gromoll et al, 2003;Müller et al, 2004a;2004b;Scammell et al, 2008). Female fertility depends on the precise execution of ovarian development, regulated allocation and maturation of oocytes, and the proliferation and differentiation of the surrounding somatic cells that occur during folliculogenesis (Elvin et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The structure, function, and regulation of FSHβ molecules have been investigated most extensively in mammals (Noguchi et al, 2006;Scammell et al, 2008) and fish (So et al, 2005;Hellqvist et al, 2006), and relatively less in birds (Shen et al, 2006;Zhao et al, 2010) and amphibians (Urbatzka et al, 2006), wherein conservation of the molecular structure of FSHβ was found, while some specific features were also reported in different species. In reptiles, the FSHβ cDNA encoding has been reported recently, for Reeves's turtle (Aizawa and Ishii, 2003) and Chinese soft-shell turtle (Chien et al, 2005), no Crocodilian FSHβ has yet been characterized.…”
Section: Introductionmentioning
confidence: 99%